BEYOND ENVIRONMENTAL COMPLIANCE : THE ROLE OF GREEN LEADERSHIP AND WORK ENVIRONMENT IN FOSTERING EMPLOYEE GREEN BEHAVIOR - Josua Parulian Sinaga; Tetra Hidayati; Irwansyah (RADJA PUBLIKA, 2026)
The transformation towards sustainable business practices positions employee green behavior as a strategic element in supporting the success of an organization's environmental agenda, particularly in sectors with high ecological risks such as the mining support services industry. Although various environmental management policies and standards have been implemented, internalizing green behavior at the individual employee level remains a challenge that requires managerial attention. This study aims to analyze the influence of green leadership and work environment on employee green behavior through the mediating role of job satisfaction at PT Barana Medayu Sejahtera, West Kutai Regency. The study used a quantitative approach with an explanatory design . The entire population was used as respondents using a questionnaire technique. Saturated sampling . Data were collected using a questionnaire and analyzed using the method Structural Equation Modeling– Partial Least Squares ( SEM-PLS ). The results of the study show that green leadership and the work environment influence employee job satisfaction and green behavior. Job satisfaction has also been shown to influence employee green behavior and is able to mediate the relationship between green leadership , work environment, and employee green behavior. These findings indicate that an organization's success in building a sustainable work culture is not only determined by formal environmental policies, but also by the leader's ability to instill ecological values and create a work environment that provides a positive work experience for employees. This research enriches the study of green organizational behavior in the context of the extractive industry while providing practical implications for companies in designing sustainability strategies that are oriented towards strengthening human aspects and an environmentally friendly work culture.